Development and Application of the 3D Model Test System for Water and Mud Inrush of Water-Rich Fault Fracture Zone in Deep Tunnels. (4th October 2021) - Guo, Yanhui; Kong, Zhijun; He, Jin; Yan, Ming
Abstract : In order to study the evolution process, damage characteristics, and occurrence mechanism of water and mud inrush disaster in deep tunnel fault zone with infiltration instability under complex conditions, a set of the three-dimensional physical model test systems of water and mud inrush flow-solid coupling in tunnel fault zones is developed. The system mainly comprises a rigid test frame, ground stress loading system, hydraulic loading system, multiple information monitoring and acquisition system, and mud and water protrusion recovery system. The system's main features are that it can meet the model's simulation of the ground stress field, water pressure, and other complex environments subjected to ground stress, and water pressure gradients can be controlled. The system is characterized by high rigidity, high-pressure strength, visualization, good sealing, and expandability. Taking the water fault zone of a well in the Dazhu Mountain Tunnel of the Darui Railway as the research object, the new fault zone and surrounding rock similar materials applicable to the flow-solid coupling model test are designed using the self-developed flow-solid coupling similar materials. The system is used for model tests to reveal the spatial and temporal changes of the surrounding rock stress field and seepage field during the tunnel excavation process. The test results show that the system is stable and reliable, and the research method and results are of guiding significance to the research of the same type of underground engineering.